2010
DOI: 10.1002/marc.201000274
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge‐Based Tailoring of Gelatin‐Based Materials by Functionalization with Tyrosine‐Derived Groups

Abstract: ---------Molecular models of gelatin-based materials formed the basis for the knowledge-based design of a polymer system with tyrosine-derived side groups enabling  interactions and hydrogen bonds and in this way creating physical netpoints. The models were validated by comparison with experimental data. Both analyses showed the desired physical interactions of desaminotyrosine (DAT) and desaminotyrosyl tyrosine (DATT) side chains. Gelatin was functionalized with DAT and DATT at 80 mol-% of the free amino g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 29 publications
1
35
0
Order By: Relevance
“…1a) were used to functionalize gelatine. The synthesis of DATT was performed as published previously [13]. For the functionalization of gelatin (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a) were used to functionalize gelatine. The synthesis of DATT was performed as published previously [13]. For the functionalization of gelatin (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Modeling studies suggested that the formation of defined physical netpoints is guided by the association of the introduced aromatic moities [12,33]. The DAT and DATT moieties can furthermore be used to increase the affinity of the gelatin matrix to hydroxyapatite particles in composites [13]. In order to evaluate their potential as biomaterials, extensive in vitro and in vivo studies of the materials should be performed, whereby comparison with the often applied, non-toxic and non-immunogenic gelatin as reference material is a sensible approach.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels, in a simplified description, may be mimicking a physiological environment for such hydrophilic molecules due to their high water content and may additionally match the mechanical properties of soft tissue. Therefore, hydrogels based on purely synthetic polymers [6] or on modified biopolymers like polysaccharides [7] [8] [9] or proteins [10] are of steadily rising relevance in drug delivery, cell delivery, and tissue engineering. While a high water content may support the stability of sensitive drugs compared to more hydrophobic polymer matrices, its drawback may be high drug diffusivity.…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin can be functionalized with desaminotyrosine (DAT) or desaminotyrosyl tyrosine (DATT) to create supramolecular gels with mechanical properties that are ruled by such the interactions of such moieties. [7,8] These materials have been previously shown to show tailored swelling degrees (Q $ 300-3000 vol%), which were dictated by the aromatic interactions between the tyrosine-derived side groups and the presence of triple helices. An important feature of these novel biomaterials is how they affect the cellular response of distinct immune relevant cells, which is reported by Roch et al [DOI: 10.1002/masy.201100048].…”
mentioning
confidence: 98%
“…Gelatin has been explored as a basis for tailorable biopolymer systems. [6][7][8] A hybrid biopolymer containing gelatin as well as chondroitin sulfate was created by functionalizing the two biopolymers with methacrylamide and then crosslinking a mixture of the two functionalized biopolymers using photoirradiation (Van Vlierberghe et al [DOI: 10.1002/masy.201100030]). The storage modulus of the resulting crosslinked biopolymer hybrids was tailorable and varied according to the composition amounts and degrees of methacrylamide substitution (G 0 ¼ 0.1-20 kPa).…”
mentioning
confidence: 99%